Can Psychological Resilience Protect the Mental Health of Healthcare Professionals during the COVID-19 Pandemic Period? - Aynur Bahar; Hatice Serap Koçak; Sevgin Samancıoğlu Bağlama; Döndü Çuhadar (Dubai Medical Journal)
It is important to protect the mental health of healthcare employees who are facing the difficult experience of a pandemic. There are proofs indicating that the state of mental well-being is related with the levels of psychological resilience. It may be important for reducing the psychological issues and emotions of burnout in healthcare professionals by increasing their psychological resilience levels during this process in which disease anxiety and fear of death develop. The purpose of this review study was to attract attention to the mental issues and psychological resilience of healthcare professionals who have the closest contact with the patients.